To the Problem of Stability of Types in Displays of Character Traits - D A Shlyakhta (Peoples' Friendship University of Russia (RUDN University), 2008)
The article considers the approaches to the individual-typical research of displays of features of the personality on the basis of A.I. Krupnov's system-functional model. The question of stability of the types singled out while studying various character traits is analyzed.